2018
DOI: 10.1002/yea.3347
|View full text |Cite
|
Sign up to set email alerts
|

The Saccharomyces cerevisiae poly (A) binding protein (Pab1): Master regulator of mRNA metabolism and cell physiology

Abstract: Pab1, the major poly (A) binding protein of the yeast Saccharomyces cerevisiae, is involved in many intracellular functions associated with mRNA metabolism, such as mRNA nuclear export, deadenylation, translation initiation and termination. Pab1 consists of four RNA recognition motifs (RRM), a proline‐rich domain (P) and a carboxy‐terminal (C) domain. Due to its modular structure, Pab1 can simultaneously interact with poly (A) tails and different proteins that regulate mRNA turnover and translation. Furthermor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 97 publications
(204 reference statements)
7
35
0
Order By: Relevance
“…Five strains were identified as M. guilliermondii and one could not be differentiated between M. guilliermondii and M. caribbica . It was shown that these two strains have an almost identical fermentation profile and are identified by its characteristic of producing coenzyme-Q9, and the separation between them is uncertain [25,26]. The species of the genus Meyerozyma belong to the phylum Ascomycota and are inserted in the clade Saccharomycotina CTG.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Five strains were identified as M. guilliermondii and one could not be differentiated between M. guilliermondii and M. caribbica . It was shown that these two strains have an almost identical fermentation profile and are identified by its characteristic of producing coenzyme-Q9, and the separation between them is uncertain [25,26]. The species of the genus Meyerozyma belong to the phylum Ascomycota and are inserted in the clade Saccharomycotina CTG.…”
Section: Discussionmentioning
confidence: 99%
“…The species of the genus Meyerozyma belong to the phylum Ascomycota and are inserted in the clade Saccharomycotina CTG. However, the phylogenetic structure of the yeasts of this group is not fully understood [24,25,26,27]. Even if the scientific advances enabled the proper identification of some yeasts from this clade, it was pointed out that one of the major problems in this identification is the range of incorrect or non-updated taxonomic annotations in public databases addressing Meyerozyma species [28,29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cytoplasmic membraneless condensates concentrate biomolecules locally in response to signal transduction to accelerate biochemical reactions (Hernández-Vega et al, 2017;Woodruff et al, 2017) or to adapt to environmental stress (Buchan et al, 2008;Kroschwald et al, 2018;Riback et al, 2017;Xie et al, 2019). When cells are stressed and enter a quiescent state, immiscible condensates store the functional macromolecules; once the stress is released, these molecules are dissolved into the dilute phase and can be utilized for various cellular functions (Franzmann et al, 2018;Marco et al, 2018;Xie et al, 2019). If these biomolecular condensates turn into gel or solid states, this will lead to a delay in or irreversible dissolving of functional macromolecules, which can be detrimental for the cell, resulting in dysfunctional or disease states, such as the pathological fibrillization of RNA-binding proteins, such as superoxide dismutase 1 (SOD1) (Grabocka and Bar-Sagi, 2016;Mateju et al, 2017;Molliex et al, 2015).…”
Section: Polarisome Components and Their Interactionsmentioning
confidence: 99%
“…RNA-binding proteins (RBPs) contain designated domains to interact with specific elements in target RNAs. For example, the RNA recognition motifs (RRMs) of the poly(A)-binding protein recognises the poly(A) tail of almost all mRNAs (Brambilla et al, 2019;Hogan et al, 2008).…”
Section: Introductionmentioning
confidence: 99%